Magnetic Nanotrap Particles Preserve the Stability of Venezuelan Equine Encephalitis Virus in Blood for Laboratory Detection - Akhrymuk, Ivan; Lin, Shih-Chao; Sun, Mei; Patnaik, Anurag; Lehman, Caitlin; Altamura, Louis; Minogue, Timothy; Lepene, Ben; van Hoek, Monique L.; Kehn-Hall, Kylene (Frontiers in Veterinary Science, 2020)
Most of the modern techniques used for identification of viral-induced disease are based on identification of viral antigens and/or nucleic acids in patient’s blood. Diagnosis in the field or in remote locations can be challenging and alternatively samples are shipped to diagnostic labs for testing. Shipments must occur under controlled temperature conditions to prevent loss of sample integrity. We have tested the ability of magnetic Nanotrap® (NT) particles to improve stability and detection of Venezuelan equine encephalitis virus (VEEV), viral capsid protein, and viral genomic RNA in whole human blood at elevated temperature and prolonged storage conditions. NT particles have previously been shown to capture and enrich multiple pathogens including respiratory syncytial virus, influenza virus, coronavirus and Rift Valley fever virus. Our study indicates that samples incubated with NT particles had detectable levels of infectious VEEV in blood equal to or greater than samples without NT treatment across all temperatures. Viral RNA detection was increased in the presence of NT particles at later time points (72h) and higher temperature (40oC) conditions. Likewise, detection of VEEV capsid protein was enhanced in the presence of NT particles up to 72h at 40oC. Finally, we intranasally infected C3H mice with TC-83, the live attenuated vaccine strain of VEEV, and demonstrated that NT particles could substantially increase the detection of VEEV capsid in infected blood incubated up to 72h at 40oC. Samples without NT particles had undetectable capsid protein levels. Taken together, our data demonstrate the ability of NT particles to preserve and enable detection of VEEV in human and mouse blood samples over time and at elevated temperatures.